Unexpected Reactivity of Red Phosphorus in Ionic Liquids - Groh, Matthias F.; Paasch, Silvia; Weiz, Alexander; Ruck, Michael; Brunner, Eike (European Journal of Inorganic Chemistry, 2015)
Red phosphorus is far less reactive than the white allotrope. On the other hand, it is easier to handle and not as toxic as white phosphorus. In the Lewis-acidic ionic liquid (IL) [BMIm]Cl·2AlCl3 ([BMIm] = 1-butyl-3-methylimidazolium), red phosphorus and elemental iodine form several iodides at moderate temperature. 31P liquid- and solid-state NMR spectroscopy was used to rationalize the reaction at various temperatures and ratios of the starting materials. Monitoring of the reaction revealed nanoscale red-phosphorus particles. In addition to this top-down formation, phosphorus nanoparticles were also obtained in a bottom-up synthesis by dissociation of P2I4 in the IL. Depending on the ratio of red phosphorus and iodine, as well as the reaction temperature, P2I4, PI3, or P2I5+ dominate. Red phosphorus readily reacts with iodine in a Lewis-acidic ionic liquid at moderate temperature. Besides iodides, phosphorus nanoparticles are formed. The latter are also obtained in a bottom-up process starting from P2I4. In situ liquid- and solid-state NMR spectroscopy reveals details of the reactions.
CRIS-Team Scopus Importer:2023-03-20
Keywords: In situ spectroscopy; Ionic liquids; Nanoparticles; NMR spectroscopy; Phosphorus